2022
DOI: 10.46483/deuhfed.955264
|View full text |Cite
|
Sign up to set email alerts
|

Okul Öncesindeki Çocukların Beslenme Alışkanlıklarının Büyüme ve Gelişmeleri Üzerine Etkisi

Abstract: Araştırma, bir ilin üç merkez ilçesinde bulunan sekiz anaokuluna devam eden okul öncesi dönemdeki çocukların beslenme alışkanlıklarını ve beslenmenin büyüme-gelişmeleri üzerindeki etkisini belirlemek amacıyla tanımlayıcı ve metodolojik bir tasarım olarak gerçekleştirildi. Gereç ve Yöntem: Araştırmanın evrenini bir ile bağlı üç merkez ilçesinde yer alan anaokullarındaki toplam 202 anasınıfında eğitim gören 4705 çocuk, örneklemini ise 335 çocuk oluşturdu. Veriler; Bilgi Formu, literatür doğrultusunda geliştirile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…In this study, it was found that 73.3% of the children were injured more than once in the last month and that 35.1% of these injuries had occurred at school. The school injury rates of children reported in studies conducted in Turkey range from 2.8 to 38.6% (11,22,24,27,28). In other countries, the rates of school injury among children have been reported to vary between 14.15 and 55.70% (23)(24)(25)(26)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, it was found that 73.3% of the children were injured more than once in the last month and that 35.1% of these injuries had occurred at school. The school injury rates of children reported in studies conducted in Turkey range from 2.8 to 38.6% (11,22,24,27,28). In other countries, the rates of school injury among children have been reported to vary between 14.15 and 55.70% (23)(24)(25)(26)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…The sociodemographic characteristics data form This form consists of 16 items questioning sociodemographic characteristics for children enrolled in the study, such as age, class, gender, education level of the mother and the father, family type, economic income level of the family, number of siblings, daily computer usage and television watching time, sports activity, number of injuries in the last month, and the area, cause, and type of the injury and where it occurred (22,26,28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation